LIXO E OS PROBLEMAS AMBIENTAIS - Maria Aparecida Santos de Oliveira; Maria Geralda de Miranda (TRF2, 2019)
Garbage is all waste generated by human activities that is considered useless and that has been disused, and is a purely human phenomenon. Strictly, in nature there is no garbage, because everything in the environment adds elements of renovation and reconstruction. The present study aims to present some aspects involved with the issue of electronic waste and the use of reverse logistics to minimize its effects on the environment. In addition to historical contextualization on the subject, the study also addressed the industrial strategy called programmed obsolescence and e-waste, its concept and its consequences for society. Issues related to Reverse Logistics were also discussed as a way to minimize the effects caused by electronic waste to the environment, as well as the analysis of current legislation on solid waste disposal.